Sustainable Development of the Slope Lands of the Russian Arctic: Investigation of the Relationship between Slope Aspects, Wind Regime and Residential Wind Comfort - Anna Korobeynikova; Nina Danilina; Nikolay Makisha (Land, 2021)
The land-use of slope terrain in the Arctic region is important and relevant, as vast territories that are reserved for proposed cities’ development have disturbed land relief. The relevance of the study is also associated with an increased interest in the development of settlements in the Arctic region, which has great territorial and resource potential. In addition to the complexity of the engineering support of such terrains, there are difficulties in organizing comfortable indoor wind comfort in the residential areas required for population well-being. The study focuses on specific conditions for residential areas design resilient to the harsh climatic conditions on difficult slope terrain to ensure the quality of life of the population in the Arctic region of Russia. The article focuses on the study of wind-chill parameters such as wind velocity and temperature for different slopes. The subject of this research is slope terrain aeration conditions of the Arctic zone in Russia. The research aim expresses the relationship between specific aeration of the slope area conditions and the layout design of residential areas to ensure comfortable living conditions for the population. The study was carried out using mathematical computational fluid dynamic (CFD) modeling of wind flows in the ANSYS Fluent program. The results of the study are graphs showing the distribution of comfort and discomfort zones in a residential area for different aeration conditions at different slope terrains. Implementation of the methodology for assessing aeration conditions for residential areas on slope terrains was carried out in the city of Murmansk. The scientific novelty of the study lies in the fact that there are no similar studies for the Arctic region in Russia. Research results can be used as a practical tool for justification of residential areas through a sample plan addressing their wind comfortability.